NOTCH ligands JAG1 and JAG2 as critical pro-survival factors in childhood medulloblastoma - Fiaschetti, Giulio (BioMed Central, 2014)
Medulloblastoma (MB), the most common pediatric malignant brain cancer, typically arises as pathological result of deregulated developmental pathways, including the NOTCH signaling cascade. Unlike the evidence supporting a role for NOTCH receptors in MB development, the pathological functions of NOTCH ligands remain largely unexplored. By examining the expression in large cohorts of MB primary tumors, and in established in vitro MB models, this research study demonstrates that MB cells bear abnormal levels of distinct NOTCH ligands. We explored the potential association between NOTCH ligands and the clinical outcome of MB patients, and investigated the rational of inhibiting NOTCH signaling by targeting specific ligands to ultimately provide therapeutic benefits in MB. The research revealed a significant over-expression of ligand JAG1 in the vast majority of MBs, and proved that JAG1 mediates pro-proliferative signals via activation of NOTCH2 receptor and induction of HES1 expression, thus representing an attractive therapeutic target. Furthermore, we could identify a clinically relevant association between ligand JAG2 and the oncogene MYC, specific for MYC-driven Group 3 MB cases. We describe for the first time a mechanistic link between the oncogene MYC and NOTCH pathway in MB, by identifying JAG2 as MYC target, and by showing that MB cells acquire induced expression of JAG2 through MYC-induced transcriptional activation. Finally, the positive correlation of MYC and JAG2 also with aggressive anaplastic tumors and highly metastatic MB stages suggested that high JAG2 expression may be useful as additional marker to identify aggressive MBs.